Crop loss and control of Pseudocercospora fruit and leaf spot of citrus in Ghana - Lawson, Lawrence E. V.; Brentu, Francis C.; Cornelius, Eric W.; Oduro, Kwadwo A.; Sedano, Maria E.; Vicent, Antonio (2018)
Pseudocercospora fruit and leaf spot (PFLS) of citrus, caused by Pseudocercospora angolensis, was recently described in Ghana and has spread in most citrus-growing areas of the country. A survey of PFLS incidence was conducted in the Eastern Region. Orchards were georeferenced and data on altitude, annual mean temperature, and annual precipitation were obtained from the WorldClim database. Fruit drop due to PFLS and other pests and diseases was evaluated in three orchards. Field efficacies of 4-week, 6-week and 8-week schedules with carbendazim + mancozeb were evaluated in the major and minor fruit production seasons. Ordinal logistic regression and generalized linear models were fitted in each case according to the nature of the data and possible overdispersion. Disease incidence in the sweet orange orchards surveyed was 25-100 %, with higher values in higher altitude areas exposed to lower temperatures and higher rainfall. PFLS was the main problem causing yield losses, associated with 84-87 % of fruit dropped on the orchard floor. PFLS severity on shoots and incidence on fruit 12 weeks after full bloom was significantly reduced by all fungicide schedules evaluated. The effects of fungicides on PFLS severity in fruit at harvest were not substantial because of intense fruit drop. The 8-week schedule showed the lowest effectiveness in reducing fruit drop and thus the 6-week schedule is preferred. Further research is needed for an integrated management of PFLS in Ghana.